(untitled) (Global Journal of Medical Research, 2022)
Nowadays neoplasms became the common surgical affections encountered in pet population especially in dogs. Among this, skin neoplasms are the most common neoplasm observed in dogs followed by mammary neoplasms. Most of the neoplasm may exhibit metastatic and paraneoplastic changes in distant sites other than primary tumor site mainly in thorax. The present study investigated on the evaluation of radiographically evident cardio-pulmonary, metastatic and paraneoplastic changes in thorax of twenty- four clinical cases of dogs of either sex belonging to different breeds and age, having superficial cutaneous and mammary neoplasm conditions presented to the University Veterinary Hospitals, Mannuthy and Kokkalai. All the dogs were undergone Fine Needle Aspiration Cytology (FNAC) of the primary tumor for neoplasm confirmation and orthogonal thoracic radiography for the assessment of each region of thorax including pleura, pulmonary parenchyma, mediastinum, trachea, cardiovascular system and extrathoracic structures were carried out. Assessment of pulmonary metastatic lesions such as size, morphology and area of distribution and atypical metastatic lesions such as calcification, secondary pneumothorax, feeding vessel signs, cavitatory lesions etc. were performed in three- view thoracic radiographs of both neoplasm conditions and observations are described here.